Potential of ZnO/ZnS as electron transport materials on Perovskite Solar Cells - Ilham Yurestira; Arie Purnomo Aji; Muhammad Feri Desfri; Ari Sulistyo Rini; Yolanda Rati (Journal of Aceh Physics Society, 2021)
Abstrak. Sel surya berbasis perovskite merupakan sel fotovoltaik generasi terakhir yang mampu memanfaatkan energi surya dengan efisiensi tinggi dan dapat difabrikasi melalui proses yang sederhana dan murah. Sejak diperkenalkannya perovskite solar cell (PSC), efisiensi konversi dayanya telah mencapai efisiensi di atas 23% dalam waktu yang relatif singkat diiringi dengan peningkatan publikasi ilmiah di bidang ini. Penggunaan semikonduktor ZnO sebagai Electron Transport Material (ETM) yang merupakan salah satu bagian utama dalam PSC mulai dilirik akibat proses pembuatan yang lebih sederhana dibandingkan TiO2. Seng oksida (ZnO) masih memiliki kelemahan yang dapat diatasi dengan penambahan ZnS untuk mengurangi rekombinasi pembawa muatan dari lapisan perovskite ke ETM. Tujuan dari artikel ini adalah untuk menyajikan tinjauan singkat tentang status terkini mengenai komposit ZnO/ZnS sebagai elektron transport material pada sel surya perovskit. Ulasan ini juga membahas peran penambahan ZnS dalam memperbaiki morfologi dalam ukuran nano dan sifat optik material sekaligus meningkatkan kinerja PSC beserta penjelasan mengenai mekanisme dasar operasi piranti untuk memberikan pemahaman yang lebih baik tentang sifat dari ZnO/ZnS sebagai ETM pada sel surya perovskit. Abstract. Perovskite-based solar cells are the latest generation of photovoltaic cells capable of utilizing solar energy at high efficiency and can be fabricated through a simple and inexpensive process. Since the introduction of the perovskite solar cell (PSC), its power conversion efficiency has reached efficiencies above 23% in a relatively short period of time accompanied by an increase in scientific publications in this field. The use of ZnO semiconductors as Electron Transport Material (ETM), which is one of the main parts of PSC, has begun to be noticed due to the simpler manufacturing process compared to TiO2. Zinc oxide (ZnO) still has a weakness which can be overcome by adding ZnS to reduce the recombination of the charge carriers from the perovskite layer to the ETM. The aim of this article is to present a brief overview of the current status of ZnO/ZnS composites as an electron transport material in perovskite solar cells. This review also discusses the role of addition of ZnS in improving morphology in nanosize and optical properties of materials as well as improving PSC performance along with an explanation of the basic mechanism of device operation to provide a better understanding of the properties of ZnO/ZnS as ETM in perovskite solar cells. Keywords: Perovskite solar cell, Composite, ZnO, ZnS dan Electron Transport Material.